2014
DOI: 10.1007/978-3-662-45231-8_23
|View full text |Cite
|
Sign up to set email alerts
|

Combining Risk Analysis and Security Testing

Abstract: A systematic integration of risk analysis and security testing allows for optimizing the test process as well as the risk assessment itself. The result of the risk assessment, i.e. the identified vulnerabilities, threat scenarios and unwanted incidents, can be used to guide the test identification and may complement requirements engineering results with systematic information concerning the threats and vulnerabilities of a system and their probabilities and consequences. This information can be used to weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…Grossmann et al [51] present an approach called Risk-Based Security Testing that combines risk analysis and risk-based test design activities based on formalized security test patterns. The involved security test patterns are formalized by using a minimal test design strategies language framework which is represented as a UML profile.…”
Section: Risk-based Security Testingmentioning
confidence: 99%
“…Grossmann et al [51] present an approach called Risk-Based Security Testing that combines risk analysis and risk-based test design activities based on formalized security test patterns. The involved security test patterns are formalized by using a minimal test design strategies language framework which is represented as a UML profile.…”
Section: Risk-based Security Testingmentioning
confidence: 99%
“…The evaluation is carried out in terms of an hypotehtical example problem applied on the NASA shuttle flight software. Großmann et al (2014aGroßmann et al ( , 2014b suggest an approach that supports both risk-driven security testing and test-driven security risk analysis. Their approach is somewhat similar to our approach in the sense that it makes use of threat scenarios to identify security tests.…”
Section: Related Workmentioning
confidence: 99%
“…The approach is supported by a tool. Großmann et al (2014b) gives an analytical evaluation of the tool, and mention that the approach will be evaluated in future case studies.…”
Section: Related Workmentioning
confidence: 99%
“…Based on the literature review, we identified six approaches that focus on risk-driven security testing. These are the approaches suggested by Xu et al [166], Murthy et al [107], Zech et al [171,172], Botella et al [15], Großmann et al [57,58], and Seehusen [135].…”
Section: Risk-driven Security Testingmentioning
confidence: 99%
“…The approaches suggested by Botella et al [15], Großmann et al [57,58], and Seehusen [135] identify security risks by making use of the CORAS risk analysis language [91]. The risk models contain threat scenarios which are used in these approaches to identify high-level test procedures.…”
Section: Risk-driven Security Testingmentioning
confidence: 99%